PENGARUH SISTEM MANAJERIAL TERHADAP SISTEM PENJAMINAN MUTU EKSTERNAL (AKREDITASI) DI SEKOLAH DASAR SDN TEMBULUN 2 - Vidia Pandji Yudha; Cucu Atikah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to measure the influence of the principal's managerial system on the external quality assurance system (accreditation) at SDN Tembulun 2. Education quality assurance is a systematic and sustainable process that aims to improve the quality of education through the evaluation of various aspects of the school, such as curriculum, teaching, and student learning outcomes. The principal has an important role in the implementation of the managerial system which involves planning, organizing, supervising, and evaluating. This study uses a correlational survey method to identify the relationship between the managerial system and accreditation results. Data was collected through interviews, observations, and document studies from principals and related staff. The results show that a good managerial system significantly affects the aspects of school input, process, and output. Effective management helps schools in meeting the set accreditation standards, including in the management of human resources, teaching, and infrastructure. These findings emphasize the importance of the role of the principal as a manager in ensuring that the school can meet the external quality assurance criteria. In conclusion, the managerial ability of school principals directly contributes to the achievement of good accreditation, so it is necessary to increase the managerial competence of school principals in an effort to improve the quality of education.